Antibacterial activity of Boesenbergia rotunda (L.) Mansf. A. extract against Escherichia coli - N. S., Zainin; Lau, K. Y.; Zakaria, M.; Radu, Son; Abdull Razis, Ahmad Faizal; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
An awareness of Escherichia coli as a foodborne pathogen and illness causing bacterium has been increased among consumers. Moreover, there is demand for natural product in order to reduce synthetic product that can cause toxic to the human. In this study, antibacterial activity, in term of MIC, MBC and killing-time curve of methanolic extract of Boesenbergia rotunda have been tested against a standard E. coli ATCC 25922 and two E. coli isolated from milk products using Clinical and Laboratory Standard Institute (CLSI) methods. The results show that B. rotunda extract was susceptible to all E. coli strains. The MIC and MBC values of B. rotunda extract against E. coli ranged 0.019 mg/mL 2.5 mg/mL and 0.039 mg/mL – 5.0 μg/mL, respectively. Killing-time curves were constructed at concentrations of 0x MIC, 1/2x MIC, 1x MIC, and 2x MIC. All E. coli strains can be killed with concentration of 2x MIC after 2 hours. The results show that B. rotunda extract has potential antibacterial activity against E. coli.